Purification of lactic acid using alkaline precipitation followed by reactive distillation - Tri Widjaja; Siti Nurchamidah; Ali Altway; Atha Pahlevi; Bayu Yusuf; Aisyah Alifatul (Journal of Fundamentals and Applications of Chemical Engineering, 2023)
Lactic acid (LA) can be applied commercially in the biodegradable polymer industry. The production of PLA biopolymers requires lactic acid with pure isomers as its raw material, therefore the process of producing lactic acid through biological fermentation pathways is preferred over through chemical synthesis processes that produce mixed (racemic) lactic acid. In general, lactic acid purification process is carried out by several methods including precipitation and distillation. Precipitation is a conventional method for separating fermented lactic acid which is carried out through 2 stages, namely neutralization and acidification. In the process of neutralizing the fermented solution, base is added to precipitate specific lactic acid and then an acidification process is carried out by adding acid to take back the precipitated lactic acid. Distillation of a raw fermented mixture can produce very pure LA. This is an effective method for separating LA from other organic acids. The reactive distillation process is a chemical process in which the chemical reaction and the distillation process are carried out in one unit. In reactive distillation, LA forms esters with alcohols in the presence of an acid catalyst. Esters have much lower boiling points than LA. Therefore, separation can be achieved by distillation. In this research, the lactic acid purification process was carried out by combining the precipitation process followed by the distillation process. The lactic acid solution obtained from the precipitation process is then mixed with ethanol and the catalyst is put into the batch distillation column system. Most of the ethanol and water come out as distillate while the residue is fed back into the distillation column system and aqueous lactic acid solution is added for the hydrolysis stage. The distillate products are ethanol and water, while lactic acid is obtained from the residue. In the esterification step, the concentration of ethyl lactate in the residue was measured, while in the hydraulic stage, the level of lactic acid in the residue was measured. In this study, the results of purification of lactic acid from the bases Ca(OH)2, NaOH, and KOH were obtained sequentially, including: 89.07%; 84.21; and 80.56%. The use of Ca(OH)2 base produces higher purity due to higher cation valence and low solubility formed between Ca(OH)2 and lactic acid so that the amount of lactic acid precipitated is greater than the other bases.